PENGARUH PERIKLANAN, HUBUNGAN MASYARAKAT, DAN WORD OF MOUTH TERHADAP EKUITAS MEREK SEPEDA MOTOR MATIC HONDA VARIO (Studi Kasus pada Mahasiswa S1 Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro) - Susilowati, Dwi; Lubis, Nawazirul; Listyorini, Sari (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2014)
This research is motivated by the decreasing of top brand award percentage of Honda Vario in matic motorcycle category from 2011-2013. It indicates that brand equity of Honda vario is decreasing. The objective of this research is to examine the effect of advertising, public relations, and word of mouth to brand equity of Honda Vario. The type of this research is explanatory research. Interviews were employed as data collecting methods by using questionnaire as research instrument. 66 respondents were chosen as sample by purposive sampling technique. Linear regression analysis and significance test were used to test the hypotheses using SPSS 15.0. The result of this study showed that all the independent variables, advertising (X1), public relations (X2), and word of mouth (X3), simultaneously or partially give positive effect to the dependent variabel of brand equity (Y). Based on these result, research suggested to Honda’s management to increase frequency of advertisements especially in print media, and to improve cooperation with mass media to generate publicity about Honda Vario.